Phytochemical profiling of Acalypha indica L. by GC-MS Analysis - Tanmoy Sinha; Dr. Abhijit Bandyopadhyay (International Journal of Pharma and Bio Sciences, 2020)
Acalypha indica L.(AI) under the Family - Euphorbiaceae, is an important medicinal plant with remarkable antibacterial and antifungal activity. Leaf extract used for the treatment of ulcer, malaria, snake bite and tuberculosis. The decoction of roots is also used as purgative, laxative and in dysentery. Main objective of the study was to identify the phytoconstituents of methanolic and ethanolic leaf extract of AI. Here fresh leaves were shade dried and freeze dried (-80?C) for seven days. 50 gms., of both leaves were extracted with HPLC grade Metahnol (99%) and Ethanol(95%) for 72 hrs. with occasional shaking. After that, both the extracts were filtered through whatmanno-1 filter paper and kept in two separate 100ml conical flasks in airtight condition at 40C. Both these extracts were subjected to GC-MS analysis for phytochemical identification. The phytochemical analysis from these extracts revealed 19 phytoconstituents from Methanolic leaf extract and 9 compounds from Ethanolic leaf extract. From this experiment of GC-MS analysis we found medicinally important phytochemicals like,β-sitosterol, Heptadecanoic acid and Squalene from Methanolic extract and Undecanoic acid, Azulene, Squalene and sitosterol from Ethanolicx leaf extract.